Statistical analysis of measured operators' finger doses in interventional radiology. Issue 2 (23rd May 2014) - Feghali, J.A.; Tagnard-Mérat, F.; Donadille, L.; Rehel, J.L.; Aubert, B.; Allodji, R.; Gauron, C.; Farah, J.; Clairand, I.
<x content-type="archive" xml:space="preserve">Abstract</x> This work suggests a classification of interventional radiology and cardiology procedures based on statistical analysis of operators' finger doses measured in routine clinical conditions. In total, 346 finger doses were measured and the observed mean finger dose per class of procedure ranged from 0.03 mSv to 1.56 mSv for Cerebral, and Bone and Joint procedures, respectively. The statistical analysis showed that the finger dose in Cerebral procedures is significantly lower than in Cardiac procedures, which was significantly lower than the rest. Furthermore, finger doses in therapeutic procedures and in close ones were significantly greater than in diagnostic procedures and in distal ones. This work also studied the statistical relation between the use of ceiling-suspended shields or leaded gloves and the extremity dose. From the set of collected and analyzed data, a finger dose classification was proposed for different criteria: procedure type (diagnostics/therapeutic), proximity (close/distal), procedure class and access route.